Vlijanie sostava biokinematiceskich cepej na assimetriju struktury dvizenij - Samsonova, A. V.; Tomilov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The influence of the structure of biomechanical circuits on the asymmetry of the structure of movements on the example of trimeric circuits (lower extremeties) at pedaling on a high-speed excercise bicycle and ??? (a trunk and the lower extremities) at rise of a bar of various weight is considered in the article. Dynamic and kinematic characteristics of movements were fixed with the use of methods of strain measurement and elrctromyography. Besides at pedaling duration of a motion cycle, and also speed of movement on the tachometer was estimated.